2006
DOI: 10.1080/14767050600924129
|View full text |Cite
|
Sign up to set email alerts
|

Normal standards of fetal behavior assessed by four-dimensional sonography

Abstract: The full range of quantitative fetal facial expressions and fetal movement patterns can be assessed successfully by 4D sonography. It is important to be able to assess normal fetal behavior throughout gestation to identify abnormal behavior before birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 29 publications
(81 reference statements)
7
76
1
Order By: Relevance
“…Yan et al [12] noted that mouthing was the most frequent facial expression between 28 and 34 weeks of gestation whereas the least frequent were scowling and sucking. These papers contradict each other about the frequency of facial patterns, which may have resulted from small sample size in each study, different study samples in all trimesters of pregnancy, and racial differences between Turkish (Yigiter et al [22]) and Japanese (Sato et al [14], There is a tendency for FGR group to have less facial expressions than AGA group especially in mouthing (p=0.057) and smiling (p=0.229), although no statistically significant difference was achieved. T.E.…”
Section: Page 7 Ofmentioning
confidence: 92%
See 1 more Smart Citation
“…Yan et al [12] noted that mouthing was the most frequent facial expression between 28 and 34 weeks of gestation whereas the least frequent were scowling and sucking. These papers contradict each other about the frequency of facial patterns, which may have resulted from small sample size in each study, different study samples in all trimesters of pregnancy, and racial differences between Turkish (Yigiter et al [22]) and Japanese (Sato et al [14], There is a tendency for FGR group to have less facial expressions than AGA group especially in mouthing (p=0.057) and smiling (p=0.229), although no statistically significant difference was achieved. T.E.…”
Section: Page 7 Ofmentioning
confidence: 92%
“…Previous studies of normal fetuses using conventional 4D ultrasound revealed some extent of such tendencies in the frequency of fetal facial expressions. Yigiter et al [22] revealed that mouthing was the most frequent facial pattern between 18 and 27 weeks of gestation, while scowling was the most prominent between 28 and 36 weeks of gestation. Sato et al [14] described that mouthing was the most common facial expression between 20 and 24 weeks of gestation.…”
Section: Page 7 Ofmentioning
confidence: 99%
“…[33][34][35]37,[39][40][41] All studies focused on the assessment of fetal facial expressions and movements, and fetal hand to face movements (Figs 6A to 8), because the viewing area was limited to that of the transabdominal probe. Kurjak et al 37 were the first to use 4D sonography to study 10 healthy fetuses for 15 minutes at 30 to 33 weeks.…”
Section: Late Second and Third Trimestersmentioning
confidence: 99%
“…49,50,52,[54][55][56][57][58][59] All studies focused on the assessment of fetal facial movements or expressions and fetal behavioral movements (mainly hand movements) (Figs 11 to 22), because the viewing area was limited to that of the transabdominal probe. "Clearly, the ability to image facial as well as hand movements and their cooccurrence is an advantage that may be related to the 4D technology.…”
Section: Late Second and Third Trimestersmentioning
confidence: 99%